AUTONOMY OF THE WILL AND CURRENT PERSPECTIVES OF ARBITRATION IN BRAZIL - Bernardo Baccon Gehlen; Fabiana Marion Spengler; Theobaldo Spengler Neto (Revista Eletrônica de Direito Processual, 2021)
The main argument of this text is the analysis of the principle of party autonomy on contracts as a decisive factor for the operation and legal certainty of the arbitration institute in Brazil. Recent laws and jurisprudence from Brazilian courts, which safeguard (or not) the agreement between parties in detriment of collective interest and unalienable rights, have been investigated through the deductive method. It is possible to conclude that - except in cases ruled by customer law - arbitration clauses set forth by the parties are binding, even when opposing public order or proven vulnerability of one of the contracting parties.